Mechanical chest compression devices at in-hospital cardiac arrest: A systematic review and meta-analysis. (June 2016) - Couper, Keith; Yeung, Joyce; Nicholson, Thomas; Quinn, Tom; Lall, Ranjit; Perkins, Gavin D.
Abstract: Aim: To summarise the evidence in relation to the routine use of mechanical chest compression devices during resuscitation from in-hospital cardiac arrest. Methods: We conducted a systematic review of studies which compared the effect of the use of a mechanical chest compression device with manual chest compressions in adults that sustained an in-hospital cardiac arrest. Critical outcomes were survival with good neurological outcome, survival at hospital discharge or 30-days, and short-term survival (ROSC/1-h survival). Important outcomes included physiological outcomes. We synthesised results in a random-effects meta-analysis or narrative synthesis, as appropriate. Evidence quality in relation to each outcome was assessed using the GRADE system. Data sources: Studies were identified using electronic databases searches (Cochrane Central, MEDLINE, EMBASE, CINAHL), forward and backward citation searching, and review of reference lists of manufacturer documentation. Results: Eight papers, containing nine studies [689 participants], were included. Three studies were randomised controlled trials. Meta-analyses showed an association between use of mechanical chest compression device and improved hospital or 30-day survival (odds ratio 2.34, 95% CI 1.42–3.85) and short-term survival (odds ratio 2.14, 95% CI 1.11–4.13). There was also evidence of improvements in physiological outcomes. Overall evidence quality in relation to all outcomes was very low. Conclusions: Mechanical chest compression devices may improve patient outcome, when used at in-hospital cardiac arrest. However, the quality of current evidence is very low. There is a need for randomised trials to evaluate the effect of mechanical chest compression devices on survival for in-hospital cardiac arrest.